Si-Accumulation In Artemisia annua Glandular Trichomes Increases Artemisinin Concentration, but Does Not Interfere In the Impairment of Toxoplasma gondii Growth - Rostkowska, Cristina; Mota, Caroline M.; Oliveira, Taísa C.; Santiago, Fernanda M.; Oliveira, Lilian A.; Korndörfer, Gaspar H.; Lana, Regina M. Q.; Rossi, Monica L.; Nogueira, Neusa L.; Simonnet, Xavier; Mineo, Tiago W. P.; Silva, Deise A.O.; et al. (Frontiers in Plant Science, 2016)
Artemisia annua is used as source of artemisinin, an active ingredient used to treat some infectious diseases such as malaria. The limiting factor to the use of artemisinin is its low concentration (from 0.01 to1.4% of dried leaf matter) achieved with the traditional cropping system. These low concentrations make artemisinin a relatively expensive drug, especially in the developing countries. Considering that silicon accumulation has never been investigated in A. annua glandular trichomes, where artemisinin is stored, this study aimed to investigate the silicon effects on A. annua physiology based on the trichome artemisinin concentration, and whether the leaf infusion from this plant is able to control Toxoplasma gondii growth. T. gondii is the etiologic agent of toxoplasmosis, a zoonotic parasitic disease whose traditional treatment shows significant side effects. The experimental design consisted of randomly planted A. annua in the soil treated with different doses of calcium/magnesium silicate (0, 200, 400, 800 and 1600 kg/ha). Analysis of foliar macronutrients showed significant increases of nitrogen content only at the highest dose of silicate. The foliar micronutrients, silicon concentrations and plant height were not affected by any of the silicate doses. However, the use of 400 kg/ha of silicate increased the trichome size, which in turn raised artemisinin concentration in leaves and the infusion. In contrast, the 800 and 1600 kg/ha doses dramatically decreased artemisinin concentration. HeLa cell treatment with the infusion of A. annua grown in the soil with silicate (400 kg/ha) decreased parasite proliferation in a dose-dependent manner when the treatment was carried out after or along with T. gondii infection. However, this effect was similar to the effect of A. annua grown in soil without silicate treatment. It can be concluded that, even though silicon applied to the soil at 400 kg/ha had a positive effect on the A. annua glandular trichome size and the artemisinin concentration, this outcome could not be directly associated with the efficiency of A. annua infusion on T. gondii growth, suggesting that other components from A. annua leaves could be acting in synergy with artemisinin.